Hands-on Kubernetes and Docker for distributed applications - Schenker, Gabriel Nicolas (Packt Publishing, 2019)
"This course shows you how Docker can be used to isolate your application services and their dependencies into a single self-contained unit that can reliably run anywhere. You will learn to build, ship and run distributed applications on any platform using Kubernetes as the orchestrator. With Docker containers, your applications can run smoothly without you worrying about the environment where they run. This aids in improved security, better scalability, resilience and fault-tolerance, making life easier for developers and operators alike who need a standardized deployment and operations model. By the end of this course you will be able to use Docker and Kubernetes to build distributed applications that are scalable, resilient, fault tolerant and secure. Furthermore you will be able to deploy these applications to any Kubernetes cluster running on any platform on premise or in the cloud."--Resource description page